Recollecting Lotte Eisner : cinema, exile, and the archive - DeCelles, Naomi (Feminist media histories, 2022)
"Recollecting Lotte Eisner provides the first in-depth examination of the remarkable transnational career of film journalist, archivist, and historian Lotte Eisner (1896-1983). From a trailblazing female film critic in interwar Berlin, to an escaped prisoner in occupied France; from chief curator at the Cinémathèque Franc̜aise, to her mythic role as the 'collective conscience' of New German Cinema--Lotte Eisner was a prolific writer and lecturer and a pivotal voice in early film and media studies. Situated at the juncture of feminist media historiography and disciplinary intellectual history, this groundbreaking book is based on extensive multilingual archival research and the excavation of a rich corpus of previously overlooked materials. Introducing samples of Eisner's writing in translation, this volume makes some of the most important contributions of a foundational scholar in the field of film studies accessible for the first time to an English-language readership"--